Geochemical studies of Setiu lagoon, Terengganu, Malaysia - Ong, Meng Chuan; Yunus, Kamaruzzaman; Bidai, Joseph (Universiti Malaya, 2009)
26 surfical sediment of Setiu lagoon were collected in order to analyze the heavy metals concentrations using the sensitive Inductively Coupled Plasma Mass Spectrometer (ICP-MS). Results from this study revealed that the average sediment concentration of lead (Pb), cobalt (Co) and copper (Cu) were 23.26 μg/g dry weight, 22.29 μg/g dry weight and 47.25 μg/g dry weight, respectively. The calculated enrichment factors (EF) for Pb, Co and Cu close to 1 can be considered to have terigeneous in sources. Generally, the concentration of Pb, Co and Cu at present is not widespread enough as to have much influence on pollution of that area.